Predictive Value of the Serum Albumin Level on Admission in Patients With Spontaneous Subarachnoid Hemorrhage - Shang, Feng; Zhao, Hao; Cheng, Weitao; Qi, Meng; Wang, Ning; Qu, Xin (Frontiers in Surgery, 2021)
Objective: The purpose of this study was to explore the effect of serum albumin levels at admission in patients with spontaneous subarachnoid hemorrhage (SAH). Methods: A total of 229 patients with SAH were enrolled in this retrospective study. The serum albumin levels were measured within 24 h and one week after onset, respectively. The patients with serum albumin levels at admission of ≤ 3.5 g/dl were divided into Hypoalbuminemia group, others were divided into control group. Death or discharge to a long-term nursing facility was considered as a poor outcome (GOS Scale ≤3). The age, gender, basic diseases (Diabetes mellitus, Hyperlipidemia, Coronary artery disease), risk factors (hypertension, smoking, excessive alcohol consumption), Hunt-Hess (H-H) grade at admission, Glasgow coma score (GCS) at admission, complications during hospitalizations (intubation, pneumonia, cerebral vasospasm, rebleeding, Delayed Cerebral Ischemia (DCI)), length of hospital stay, length of intensive care unit (ICU) stay, in-hospital mortality, survival rate and outcome at discharge as well as the 6-month follow-up outcome between the two groups were compared. Results: The average age was higher, the number of patients suffering from excessive alcohol consumption was greater and the mean Glasgow coma score at admission was lower in the hypoalbuminemia group in comparison with control group (p < 0.001). Moreover, the ratio of patients with H-H grade I at admission in the hypoalbuminemia group was lower than the control group (p < 0.05). Patients with hypoalbuminemia were more likely to have intubation, pneumonia and Cerebral vasospasm than those with normal albumin level at admission (p < 0.001). Furthermore, the lengths of hospital stay and ICU stay were longer in the hypoalbuminemia group than the control group (p < 0.001). Although hypoalbuminemia at admission did not impact in-hospital mortality (p = 0.350), it drastically raised the poor outcomes at discharge (p < 0.001). In in-hospital outcomes, the number of patients with severe disability was increased and the recovery rate was decreased in the hypoalbuminemia group than the control group (p < 0.001). Conclusions: Hypoalbuminemia may induce poor prognosis in patients with SAH.